If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 9(4x + 6) = 5 + -4(9x + -6) Reorder the terms: 8 + 9(6 + 4x) = 5 + -4(9x + -6) 8 + (6 * 9 + 4x * 9) = 5 + -4(9x + -6) 8 + (54 + 36x) = 5 + -4(9x + -6) Combine like terms: 8 + 54 = 62 62 + 36x = 5 + -4(9x + -6) Reorder the terms: 62 + 36x = 5 + -4(-6 + 9x) 62 + 36x = 5 + (-6 * -4 + 9x * -4) 62 + 36x = 5 + (24 + -36x) Combine like terms: 5 + 24 = 29 62 + 36x = 29 + -36x Solving 62 + 36x = 29 + -36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36x' to each side of the equation. 62 + 36x + 36x = 29 + -36x + 36x Combine like terms: 36x + 36x = 72x 62 + 72x = 29 + -36x + 36x Combine like terms: -36x + 36x = 0 62 + 72x = 29 + 0 62 + 72x = 29 Add '-62' to each side of the equation. 62 + -62 + 72x = 29 + -62 Combine like terms: 62 + -62 = 0 0 + 72x = 29 + -62 72x = 29 + -62 Combine like terms: 29 + -62 = -33 72x = -33 Divide each side by '72'. x = -0.4583333333 Simplifying x = -0.4583333333
| 99/7x= | | (8x^2-6x-31)+(6x^2+9x)= | | -4/9*x=8 | | z/3-5/4 | | P(3≤x≤6)=P((3-3)/1.5≤z≤(6-3)/1.5) | | -3+6(6x-6)=6-6(6x+4) | | f(x)=0.5(x-1)+1 | | (a/9)=(a-1)/8 | | (x/18)=-5/6 | | 12x=1x+9 | | 20t^2+18t-5=0 | | 15-5x-8-6x=11-2x+2 | | -(3y+3)-(-2y-4)=-2 | | y^2+18y-81=0 | | 12/15=x/32 | | x/14=12/7 | | 6/7t=48 | | (((x-5)/5)-1)=((x-13)/6) | | 11-3x=-6x+2 | | 3z+7=z+10 | | cot(x)=2.4 | | log(8)(k-8)=2 | | x^3-x^2+15*x+17=0 | | V=Bcy | | 4sin(2x)+2=0 | | 0.2x+4.4=3.3 | | (1128*2)+(120*3)=x+(x*0.2) | | -2(a-6)=-36 | | z=0.06-50/6 | | 70(-8/5) | | 2y+3=33 | | x^2-4x+4+x^2-18x+81=x^2 |